Validation of Hemostasis and Coagulation Assays: Recommendations and Guidelines - Marlar, Richard A.; Gausman, Jana N.; Engel, James W. (Seminars in Thrombosis and Hemostasis, 2014)
The clinical hemostasis laboratory is a complex testing arena which employs numerous coagulation assays and spans several different test methodologies. Adding further complexity, these test results are expressed in a wide variety of unique units (concentration, activity, time, percentage, and ratio). Unfortunately, many of these reference values are derived from a local plasma pool or manufacturer's standards, as there are few established international standards. These three main issues complicate the validation and performance of the coagulation testing. Before an assay can be introduced into clinical use, both analytical and clinical performance parameters must be validated or verified using the standard validation procedures of the laboratory. This article summarizes the initial evaluation and validation processes of the coagulation laboratory, which sometimes can be difficult concepts to implement. A standardized validation protocol is described in this article and, if used, will help to objectively evaluate the assay performance and determine if it meets acceptable laboratory criteria.
Keywords: hemostasis assay; coagulation assay; test validation; specificity; sensitivity; accuracy; precision